Las dos fuentes en las laminillas órficas (Minerva. Revista de Filología Clásica, 2019)
In the two Orphic lamellae examined, the same fountain is said to be «on the right» or «on the left» according to the position of the viewer (as is the case with the bedroom window in the famous short story by Wodehouse): it is on the right if one looks at the front of one or more rows of houses, but on the left if one looks out from the front of the said houses.